1997
DOI: 10.1056/nejm199702273360902
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled Nitric Oxide and Persistent Pulmonary Hypertension of the Newborn

Abstract: Inhaled nitric oxide improves systemic oxygenation in infants with persistent pulmonary hypertension and may reduce the need for more invasive treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
379
0
21

Year Published

1997
1997
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 802 publications
(409 citation statements)
references
References 17 publications
2
379
0
21
Order By: Relevance
“…Because RCTs have shown that iNO reduced the need for rescue therapy with ECMO in many newborns with PPHN, 206,242,243 iNO was considered a promising therapy for the treatment of acute PH in CDH. 244 Early reports demonstrated that iNO can improve oxygenation and PH in some infants with severe CDH shortly after birth.…”
Section: Pah-specific Therapymentioning
confidence: 99%
“…Because RCTs have shown that iNO reduced the need for rescue therapy with ECMO in many newborns with PPHN, 206,242,243 iNO was considered a promising therapy for the treatment of acute PH in CDH. 244 Early reports demonstrated that iNO can improve oxygenation and PH in some infants with severe CDH shortly after birth.…”
Section: Pah-specific Therapymentioning
confidence: 99%
“…This effect of endogenous NO in the human respiratory tract, derived from the upper airways, was termed ‘aerocrine’ to illustrate the airborne transport of a biological messenger [39]. Since it is known that exogenous NO gas delivered to inhaled air dilates vessels in the lung, leading to increased oxygen uptake and a reduction in pulmonary vascular resistance [46], the vasodilating effect of NO is used for the treatment of pulmonary hypertension [40,47]. …”
Section: Function Of Nomentioning
confidence: 99%
“…INO has been used in the therapy of several pediatric and adult lung diseases ( [69][70][71] for review). A major established therapeutic use of INO is in pulmonary hypertension of the newborn [69,[72][73][74]. INO has also been shown to reduce pulmonary artery pressures and/or pulmonary vascular resistance in a number of animal models of acute pulmonary injury [75][76][77][78][79][80], making it relevant for patients with ALI/ARDS.…”
Section: Inhaled Nitric Oxide (Ino)-nitricmentioning
confidence: 99%